Reframing Smart Governance in West Java: Embedding New Public Service Values in Digital Transformation - Rukayat, Yayat; Kushendar, Deden Hadi; Sopandi, Encep (Jurnal Manajemen Pelayanan Publik, 2025)
This study explores the implementation of smart governance within the paradigm of the New Public Service (NPS) in the context of digital transformation in West Java Province. Unlike previous studies that primarily emphasize technical efficiency, this research offers novelty by reframing smart governance through NPS values such as citizen engagement, co-creation, transparency, and public accountability. Employing a concurrent mixed-methods design, the study integrates quantitative and qualitative approaches to provide a comprehensive understanding of the dynamics between digital public service innovation and citizen-centered governance. The quantitative component involved 278 respondents who assessed the effectiveness, inclusivity, and responsiveness of digital public services using structured questionnaires, while the qualitative component drew insights from in-depth interviews with eight key informants, including policymakers, bureaucrats, community leaders, and digital governance experts. The findings reveal that although digital initiatives in West Java have significantly improved service efficiency and accessibility, gaps remain in citizen participation, equitable data access, and institutional adaptability. The study contributes to the theoretical discourse on digital governance by proposing a localized framework of smart governance rooted in democratic values and collaborative public service delivery. Practically, it recommends strengthening digital literacy, institutional coordination, data protection policies, and inclusive participatory mechanisms to foster trust-based and citizen-centric digital governance in West Java.